Relationships between balance and functional performance in football players - Erkmen, N.; Taskin, H.; Sanioglu, A.; Kaplan, T.; Bastürk, D. (Journal of Human Kinetics, 2010)
The aim of the present study was to examine the relationships between balance performance as measured by the Balance Error Scoring System and functional performance in football players. Twenty-two football players from University League Final Group in Turkey (age 23.05 +/- 1.65 years, height 176.58 +/- 6.99 cm, weight 68.80 +/- 7.00 kg) volunteered to participate in the study. Postural performance was measured by the Balance Error Scoring System (BESS). For functional performance, standing broad jump, triple-hop, vertical jump, four-line sprint and three-corner run test were used. There was not a statistically significant relationship among the all BESS scores and triplehop in non-dominant leg, power, four-line sprint, and three-corner run performances (p<0.05). Triple-hop in dominant leg performance correlated with foam surface, tandem leg and total BESS score (r = 0.755, p < 0.01; r = 0.664, p < 0.05; r = 0.713, p< 0.01, respectively). Standing broad jump performance correlated with foam surface, tandem leg and total BESS score (r = 0.737, p < 0.01; r = 0.692, p < 0.05; r = 0.617, p< 0.05, respectively). There was a statistically significant relationship among the single leg BESS score and vertical jumping performance (r = 0.596, p<0.05). In conclusion, the activities requiring explosive power may reflect the ability of managing a balanced posture but the activities in which time period is longer may not.